Corticosteroid treatment for refractory intracranial hypertension: a rescue therapy in patients with severe traumatic brain injury with contusional lesions—a feedback - Menat, Sophie; Jacquens, Alice; Mathon, Bertrand; Bonnet, Baptiste; Schotar, Eimad; Boch, Anne-Laure; Carpentier, Alexandre; Puybasset, Louis; Abdennour, Lamine; Degos, Vincent (Acta neurochirurgica, 2023)
Introduction Refractory intracranial hypertension (rICH) is a severe complication among patients with severe traumatic brain injury (sTBI). Medical treatment may be insufficient, and in some cases, the only viable treatment option is decompressive hemicraniectomy. The assessment of a corticosteroid therapy against vasogenic edema secondary to severe brain injuries seems interesting to prevent this surgery in sTBI patients with rICH caused by contusional areas. Methods This is a monocentric retrospective observational study including all consecutive sTBI patients with contusion injuries and a rICH requiring cerebrospinal fluid drainage with external ventricular drainage between November 2013 and January 2018. Patient inclusion criterium was a therapeutic index load (TIL; an indirect measure of TBI severity) > 7. Intracranial pressure (ICP) and TIL were assessed before and 48 h after corticosteroid therapy (CTC). Then, we divided the population into two groups according to the evolution of the TIL: responders and non-responders to corticosteroid therapy. Results During the study period, 512 patients were hospitalized for sTBI, and among them, 44 (8.6%) with rICH were included. They received 240 mg per day [120 mg, 240 mg] of Solu-Medrol for 2 days [1; 3], 3 days after the sTBI. The average ICP in patients with rICH before the CTC bolus was 21 mmHg [19; 23]. After the CTC bolus, the ICP fell significantly to less than 15 mmHg ( p < 0.0001) for at least 7 days. The TIL decreased significantly the day after the CTC bolus and until day 2. Among these 44 patients, 68% were included in the responder group ( n = 30). Discussion Short and systemic corticosteroid therapy in patients with refractory intracranial hypertension secondary to severe traumatic brain injury seems to be a potentially useful and efficient treatment for lowering intracranial pressure and decreasing the need for more invasive surgeries.